(untitled) (Journal of the College of Basic Education, 2024)
The Al-Bataeh region in southern Iraq is considered one of the most important areas where the most important conflicts and revolutions took place, while Al-Abbasiya, at the hands of aid, caused labor and forced labor in those areas, which was characterized by the presence of marshes, flats, and flats, which helped organize those revolutions, the most important of which were the Al-Zat revolution in the year 205 AH and the Zanj revolution in the year 255 AH. Likewise, the revolution of Imran bin Shaheen in the year 329 AH... and the Abbasid state was able to eliminate those revolutions after a long struggle and after they threatened the prestige of the state and its continuity.